Association between niacin intake and osteoarthritis in the US population based on NHANES 1999–2018 - Xiaofeng Lv; Xinmin Deng; Rui Lai; Shanshan Liu; Zihao Zou; Renhong Wan; Xuechun Dai; Yalan Luo; Ying Li (Scientific Reports)
Abstract The relationship between niacin and osteoarthritis (OA) is not clear. Using a retrospective cohort study from the National Health and Nutrition Examination Survey (NHANES), this study aimed to investigate the association between niacin intake and osteoarthritis. This study conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey 1999–2018 to investigate the association between niacin intake and osteoarthritis. The association between niacin and osteoarthritis was assessed using univariate and multivariate weighted logistic regression models and restricted cubic spline curves (RCS). Nonlinear correlation is analyzed by fitting smooth curve. In this study, 30,620 participants were examined, with 1,864 individuals diagnosed with osteoarthritis, resulting in a prevalence of 5.74%. Utilizing multivariate weighted logistic regression, a consistent inverse relationship between Niacin and osteoarthritis was observed (OR = 0.99, 95% CI: 0.98–0.99, P = 0.003). When Niacin was treated as a categorical variable, the highest Niacin quartile (Q4) exhibited a 33% reduced risk of osteoarthritis compared to the lowest quartile (Q1) (OR = 0.67, 95% CI: 0.53–0.83, P = 0.0004). The restricted cubic spline analysis revealed a non-linear association between Niacin and osteoarthritis risk (non-linear P = 0.022), with 33.53 as the inflection point. Subgroup analyses further highlighted a stronger inverse relationship between Niacin and osteoarthritis in Non − Hispanic Black and other Race patients. The results showed a negative linear relationship between niacin intake and OA risk. By increasing the intake of niacin-rich foods, the risk of osteoarthritis can be reduced, providing ideas for the prevention and treatment of osteoarthritis. Further future studies are recommended to validate our findings.